Synthesis of Green Palm Oil Mill Fuel Ash Zeolites (G-POMFAZ) Using Hydrothermal-Alkaline-Ultrasound Technique (HAUT) - Said, N.; R. M., Yunus; Abdul Aziz, Mohd Azoddein; Syafiqah , A. Khairuddin; Hajar Athirah, M. Sukri; Chuah, C. Wooi (Knowledge Transfer Centre, USM, 2016)
The tremendous fuel ashes are deserted by palm oil industries into environment were not processed for commercializable products such as zeolites, etc. There are a few methods for zeolites synthesis, such as molten-salt, sol-gel, etc., but it takes considerable time, extensive set up and needs to high cost, thus this work aims to solve this issues by knowledge transfer of hydrothermal-alkaline-ultrasound technique (HAUT) for palm oil mill fuel ash (POMFA) based zeolites synthesis as sustainability and green material processing technology initiatives. The knowledge transfer methods of the POMFA characterization and analysis procedure completed via talks, workshop, practical, exercise and data analysis. The analysis of POMFA using Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD), Brunauer-Emmett-Teller (BET), Fourier Transformed Infra Red (FTIR), and X-Ray Flourescent (XRF) for composition approval has been conducted. The XRF result reveals 37.92 % silicon dioxide and 3.42% aluminium oxide etc. as major components typically used in the manufactures of zeolites. Next, the green technology transfer for zeolites synthesis from POMFA via HAUT utilization, process parameter effect, analysis equipments and operational procedure has been achieved. The highest Green Palm Oil Mill Fuel Ash Zeolites (G-POMFAZ) using HAUT was found at the operation condition of POMFA-akaline ratio of 1:2, ultrasonic exposure time of 2.5 h, medium temperature of 80°C, irradiation power of 800 W and frequency of 45 kHz. The synthesized G-POMFAZ can be considered as an alternative material for industrial application, like construction, petrochemical, etc. The knowledge transfer program via training and dissemination of morphology analysis of G-POMFAZ was directed to the company staff. The staff knowledge is drastically increased on the POMFA characterization and zeolites synthesis. The project contributes also to the reduction of the CH Biotech-wastes and contaminated particulate matter gradually.